2015
DOI: 10.1177/2325967115s00139
|View full text |Cite
|
Sign up to set email alerts
|

Does Revision Hip Arthroscopy Result in Improved Clinical Outcomes? - A 2-Year Clinical Follow-up On All Revision Hip Arthroscopies Performed at a High Volume Referral Center

Abstract: Objectives:The purpose of this study was to evaluate clinical outcomes, pain, and patient satisfaction following revision hip arthroscopy at a high volume referral center with a minimum 2-year follow-up.Methods:During the study period, April 2008 to October 2011, data was prospectively collected on all patients undergoing revision hip arthroscopy. All patients were assessed pre- and post-operatively with 4 patient-reported outcome (PRO) measures: the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
84
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 21 publications
8
84
3
1
Order By: Relevance
“…Over the past decade, studies have demonstrated that outcomes after hip arthroscopy for the treatment of femoroacetabular impingement can lead to predictable pain relief, improvement of hip function, and a high return to baseline level of function 13,16,22,23,31,32 . Despite the substantial increase in recent publications analyzing hip arthroscopy and femoroacetabular impingement, there remains a paucity of literature discussing differences in hip arthroscopy according to sex or age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, studies have demonstrated that outcomes after hip arthroscopy for the treatment of femoroacetabular impingement can lead to predictable pain relief, improvement of hip function, and a high return to baseline level of function 13,16,22,23,31,32 . Despite the substantial increase in recent publications analyzing hip arthroscopy and femoroacetabular impingement, there remains a paucity of literature discussing differences in hip arthroscopy according to sex or age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, understanding which patients may be at increased risk for complications [15][16][17][18][19][20][21] and reoperation is paramount and may assist clinicians in choosing alternative treatment options. Recently, Gupta et al 22 analyzed 595 patients undergoing hip arthroscopy at a mean follow-up of 29 months and found that increased patient age was significantly associated with increased total hip arthroplasty conversion rates. In addition, acute injury, microfracture, increased age, and female sex were associated with an increased need for revision arthroscopy.…”
mentioning
confidence: 99%
“…Gupta et al 2 reported statistically significant improvements in clinical survey scores after 2 years in 595 patients undergoing primary hip arthroscopy at a single institution. A 2007 systematic review comparing arthroscopy with open and mini-open procedures found the former to be equally efficacious with a lower rate of complications, 3 and Byrd et al 4 have shown continued improvements through 10-year follow-up.…”
mentioning
confidence: 99%
“…Patients undergoing hip arthroscopy for FAI and labral injuries showed excellent short-term results, significant increased clinical outcomes, high return-to-sport rates and few complications 17,18 . Due to the complex anatomic relationship between the iliopsoas tendon and the anterior surface of the hip joint, intra-articular pathologies can be associated with a iliopsoas tendinopathy and vice versa.…”
Section: Discussionmentioning
confidence: 93%